2008
DOI: 10.1177/147776060802400301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Re-Compounding on the Properties of Polypropylene / Wood Flour Composites

Abstract: Two different mixers were used for re-compounding of wood fl our / polypropylene composites (WPC): internal Banbury mixer and co-rotating twin-screw extruder. Five cycles in an internal mixer and twelve cycles in an extruder were performed on WPC in order to compare the properties of composites. After 3 cycles in an internal mixer, an increase of the WPC mechanical properties (tensile, fl exural and impact strength) and a decrease of water uptake was observed. Further increase of the number of cycles in an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Aesthetics and mechanical properties are not as good as natural wood, but if compared to other engineered wood products, such as medium‐density fiberboard or particleboard, WPC performs better. Finally, WPC is recyclable like all thermoplastics: although it may be difficult to reprocess, Viksne and Rence and Shahi et al have found that the mechanical properties do not decay too much with the number of reprocessing cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Aesthetics and mechanical properties are not as good as natural wood, but if compared to other engineered wood products, such as medium‐density fiberboard or particleboard, WPC performs better. Finally, WPC is recyclable like all thermoplastics: although it may be difficult to reprocess, Viksne and Rence and Shahi et al have found that the mechanical properties do not decay too much with the number of reprocessing cycles.…”
Section: Introductionmentioning
confidence: 99%